Refugial origin and postglacial colonization of holarctic reindeer and caribou - Knut H. Røed (Rangifer, 2005)
The classification and colonization of reindeer and caribou (Rangifer tarandus) was assessed from analysis of both proteins, nuclear DNA and mitochondrial DNA. I demonstrate that the current subspecies designations are not compatible with the differentiation at these markers, suggesting that the morphological differences among extant subspecies did not evolve in separate glacial refugia. Thus, morphological differences among extant subspecies probably evolved as adaptive responses to post-glacial environmental changes. An exception to this is the North American woodland caribou, where all three marker systems support a subspecies-specific refugium as the ancestral origin of these animals. Three major mtDNA haplogroups reported, represent three separate origins of the species during the last glaciation. The most influential origin has contributed to the gene pool of all extant subspecies, suggesting the existence of a large and continuous glacial population ranging across extensive areas of tundra in Eurasia and Beringia. The North American tundra forms (R.t. granti and groenlandicus) and the arctic forms (R.t platyrhynchus, R.t pearyi and R.t eogroenlandicus) almost exclusively comprise haplotypes of such an origin. Another small and isolated refugium seems to have arisen in western Eurasia in close connection to the extensive ice sheet that covered Fennoscandia. The two Eurasian subspecies R.t. tarandus and R.t. fennicus appear to have a diphyletic origin as both the putatively small and isolated Eurasian refugium and the large Beringia refugium have contributed to their gene pools. A third distinct and geographically well-defined refugial area was probably located south to the extensive North American continental ice sheet from where the ancestors of the present North American woodland caribou (R.t. caribou) likely originated.